(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2025)
The paper primarily derives its feet to ascertain pedagogical concerns on using technology for vocational education and training (VET) for different skill development programmes in institutions during COVID times. The educational institutions cutting across levels have massively used technology for teaching and learning during the pandemic period (COVID-19) to transact the curriculum prescribed for learners. The use of technology for transaction of curricular practices is also no way exception to the skill training programmes as well though it is supposed to be focussed on hands-on-training. The potentiality of using technology has been well recognised in the context of TVETway back 2005 by European Union as it states “the development of IT and e-learning in iVET institutions is closely connected with broader issues such as the evolution of the information society, the lifelong learning paradigm and the general development of secondary education” (EU 2005). Similarly, the researches have proved that “if access to TVET is to increase, new ways of developing and delivering courses must be explored. TVET must be taken outside of the classroom and into the communities, the workplaces and the homes of the students. Traditional ways of thinking about TVETmust be put aside and different ways of packaging and delivering knowledge and skills must be developed” (Hampton, C. and Bartram, J. 2002:63). The present paper strives to look into some of the issues and challenges in using technology for TVET with emphasis on accessibility, facilitation of teaching and learning, sustaining learner’s motivation, addressing social and economic issues & challenges and ensuring teaching-learning process more enjoyable, including addressing institutional developmental plans.